Legal Protection for Children Born from Unregistered Marriage in Medan City and Its Socialization Through Website - Sitompul, Roswita; Alesyanti, A; Hartono, H; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
Children is the hope of the nation that must be fought for, protected and guaranteed for its future. The State’s survival depends on the young generation of today, so the child must be legally protected, not to mention children born of unregistered marriages. From the biological side of the child is the biological child of both parents, only the marriage of both parents are not registered under applicable law. This research is normative juridical which is descriptive which its data collecting is done by questioner, interview, observation, population of purposive sampling which is related to this research. The results show that there is no legal protection for children born from unregistered marriage, especially the right to welfare, education, decent living, although there are many regulations that regulate the rights of children but not touched, even in reality in terms of practice there is discrimination of children , the government should establish a new regulation to regulate legal protection for children born of unregistered marriages. So we do not hear anymore, the suffering that children experience with their future as a result of the discrimination of the State’s treatment of Unregistered children. The result of this research was expected to be known to many people through socialization by using the website Â